The Dutch employment miracle? A comparison of employment systems in the Netherlands and Germany - Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
In the 1980s, the Netherlands had one of the highest unemployment rates in the European Community, Germany one of the lowest. Today, the reverse is true. Is there a Dutch employment miracle? If so, how can it be explained? This essay is an attempt to answer these questions in seven steps. Beginning with the development of an analytical framework within which employment systems are compared, the author measures the performance of the two labour markets and economies, paying particular attention to the role of labour market policy in the process of adapting to structural change. It is shown that the Netherlands has an interesting new configuration in which the advantages of competitive and coordinated capitalism are combined with a modernised form of the welfare state. A key shortcoming of both employment systems remains the hitherto highly passive character of employment redistribution. Transitional labour markets would be a more appropriate strategy for redistributing employment in order to link long-term social needs and economic efficiency. On the whole, however, developments in the Netherlands point much more clearly than those in Germany to a path along which the European model could move. – – In den achtziger Jahren war die Arbeitslosenquote in den Niederlanden noch eine der höchsten in der Europäischen Gemeinschaft, und Deutschland hatte eine der niedrigsten Quoten. Heute ist es umgekehrt. Gibt es ein niederländisches Beschäftigungswunder und wie ist es zu erklären? Der folgende Essay versucht, diese Frage in sieben Schritten zu beantworten. Nach der Entwicklung eines analytischen Bezugsrahmens zum Vergleich von Beschäftigungssystemen wird die Performanz der beiden Arbeitsmärkte und Volkswirtschaften gemessen. Besondere Aufmerksamkeit gilt der Rolle der Arbeitsmarktpolitik im Anpassungsprozeß an den Strukturwandel. Der bewertende Vergleich der Beschäftigungssysteme ergibt, daß sich in den Niederlanden eine interessante neue Konfiguration herausbildet, in der die Vorteile des Konkurrenz- und Konkordanzkapitalismus mit einer modernisierten Form des Wohlfahrtsstaats verknüpft werden. Ein zentrales Defizit beider Beschäftigungssysteme bleibt der bisher stark passive Charakter der Arbeitsumverteilung. Übergangsarbeitsmärkte wären eine geeignetere Strategie der Arbeitsumverteilung, um langfristig soziale Belange mit wirtschaftlicher Effizienz zu verbinden. Insgesamt zeigt die Entwicklung in den Niederlanden jedoch deutlicher als in Deutschland in eine Richtung, in die sich das Modell Europa bewegen könnte.
Keywords: 330